A Control Strategy of IGBT Junction Temperature for Electric Vehicle during Start-up Process - LIU Peng; CHEN Zhichu; TANG Xionghui; ZHANG Siyu; ZHANG Shibing; GU Qiang (Kongzhi Yu Xinxi Jishu)
In the start-up process of electric vehicles, due to low output current frequency of controller, junction temperature fluctuates seriously when output torque is full, which is easy to cause the IGBT chip to have too high junction temperature, and will affect reliability and service life of the module. Aiming at the above problems, a control strategy of IGBT junction temperature in the start-up process of electric vehicle based IGBT speed feedback is proposed. By analyzing the mathematical relationship among speed, current and switching frequency during the starting process, a torque release function is constructed according to the speed feedback, and the upper limit of torque is constantly released to control the junction temperature on the basis of improving the dynamic performance of the vehicle as much as possible. Finally, the feasibility of the proposed control strategy is proved by the Matlab simulation and the measured data of black module.